Higher nitrification and lower consumption drive higher N2O effluxes in estuarine than non-estuarine mangrove wetlands - Conghe Zhang; Wei Ke; Caitlin Hicks Pries; Fernando Montaño López; Joanna Ridgeway; Liming Wang; Yimeng Yin; Shengbin Ye; Shanshan Song; Xinyu Dou; Xinao Guo; Miao Li; et al. (Environmental Research Letters)
Mangrove ecosystems are highly productive, sequestering large amounts of carbon from the atmosphere while emitting relatively low levels of greenhouse gases. Large amounts of organic matter and nitrogen from river discharge may stimulate production and emission of greenhouse gases including N _2 O, thus reducing the blue carbon storage capacity of mangrove wetlands. However, it is unclear how the input of organic matter and nitrogen affect the emission fluxes of these greenhouse gases in mangrove wetlands. In this study, we compared the effluxes of N _2 O between the estuarine and non-estuarine mangrove wetlands near the seven major rivers on Hainan Island of China. The averaged N _2 O emission flux in the estuarine mangrove wetlands was 6.9 times than the non-estuarine mangrove wetlands. In the non-estuarine mangrove wetlands N _2 O emission flux increased significantly with total nitrogen content in the sediments. In contrast, organic carbon (OC)/organic nitrogen (ON) ratios were associated with N _2 O emissions in the estuarine mangrove wetlands. As rivers bring in more organic matter with high ON content, more N _2 O emissions occur in estuarine areas. OC in sediments are from different sources between estuary (fresh water dissolved OC (DOC)) and non-estuary (marine DOC) area. A higher OC/ON ratio leads to higher nitrification and lower N _2 O consumption enzyme activities in estuary areas compared with non-estuaries, which contributes extra N _2 O fluxes. Our study provides a direct process assessment of the response of natural N _2 O emissions to sediment chemistry changes caused by river inputs.